Similarity between the 38-kilodalton lipoprotein of Treponema pallidum and the glucose/galactose-binding (MglB) protein of Escherichia coli. - Becker, P S (1994)
The recent discovery that abundant and immunogenic lipoproteins constitute the integral membrane proteins of Treponema pallidum has prompted efforts to investigate their importance in the physiology and ultrastructure of the organism and in immune responses during infection. Earlier studies identified a 38-kDa lipoprotein of T. pallidum believed to be specific to the pathogen. In the present study, monoclonal antibodies generated against the 38-kDa lipoprotein of T. pallidum reacted with cognate 37-kDa molecules in the nonpathogens Treponema phagedenis, Treponema denticola, and Treponema refringens. Cloning and expression of the 38-kDa-lipoprotein gene of T. pallidum in Escherichia coli revealed that the recombinant product displayed a slightly larger (39-kDa) apparent molecular mass but remained reactive with anti-38-kDa-protein monoclonal antibodies. The recombinant product was processed and acylated in E. coli. DNA and amino acid sequence analyses indicated an open reading frame encoding 403 amino acids, with the first 25 amino acids corresponding to a leader peptide terminated by a signal peptidase II processing site of Val-Val-Gly-Cys. The predicted mature protein is 378 amino acids in length with a deduced molecular weight of 40,422 (excluding acylation). Southern blotting failed to demonstrate in nonpathogenic treponemes genomic sequences homologous with the 38-kDa-lipoprotein gene of T. pallidum. Computer analysis revealed that the 38-kDa lipoprotein of T. pallidum had 34.2% identity and 58.9% similarity with the glucose/galactose-binding protein (MglB) of E. coli and Salmonella typhimurium. Furthermore, of the 19 amino acids of MglB involved in carbohydrate binding, the 38-kDa lipoprotein had identity with 11. These studies have allowed the first putative functional assignment (carbohydrate binding) to a T. pallidum integral membrane protein. Recognition of this potential physiological role for the 38-kDa lipoprotein underscores the possibility that the membrane biology of T. pallidum may more closely resemble that of gram-positive organisms, which also utilize lipoproteins as anchored transporters, than that of gram-negative bacteria to which T. pallidum often is analogized.